The Influence of Interpersonal Sensitivity on Smartphone Addiction: A Moderated Mediation Model - Lin, Li; Wang, Xiaochen; Li, Qing; Xia, Bingnan; Chen, Peihong; Wang, Wei (Frontiers in Psychology, 2021)
Smartphone addiction is a behavioral dependence characterized by excessive or compulsive internet use and a preoccupation with and loss of control over this use that interferes with an individual’s daily functioning and results in negative mental processes and subsequent social consequences. Smartphone addiction can negatively impact physical and mental health as well as academic performance, sleep quality and even interpersonal interaction and relationships. Based on the compensatory internet use theory, this study explores the relationship between interpersonal sensitivity and smartphone addiction in College students and constructed a moderated mediation model. A sample of 881 college students was tested using the Interpersonal Sensitivity Scale (IPSM), Smart Phone Addiction Scale (SAS-C), Loss Fear Scale (FoMOs) and Relational Self-Construal Scale (RISCS). We used AMOS 21.0 to conduct a confirmatory factor analysis and employed SPSS 19.0 to test our hypotheses. The results indicated that: (1) Interpersonal sensitivity was positively related to the fear of missing out and smartphone addiction; (2) The fear of missing out mediated the relationship between interpersonal sensitivity and mobile phone addiction; (3) Relational self-construal moderated interpersonal sensitivity and the fear of missing out; (4) Relational self-construal moderated the mediating effect of the fear of missing out on the relationship between interpersonal sensitivity and smartphone addiction. We concluded that the fear of missing out and relational self-construal play a moderated mediation effect on the relationship between smartphone addiction and interpersonal sensitivity. Our findings provided some theoretical implications. On the one hand, we provided a new approach for the study of smartphone addiction. On the other hand, we also introduced a theoretical basis for psychotherapy and intervention of smartphone addiction. For example, for students with high interpersonal sensitivity, this study indicates that games, group discussions, role-playing and other forms of activities can be beneficial in an intervention setting.